MATRICES IN THE EDUCATION OF THE FUTURE TRANSPORT ENGINEERS WITH SUPPORT OF MATLAB - Kulička, Jiří; Matoušová, Ivana (International Association of Technology, Education and Development (IATED), 2019)
This study directly follows on the articles dealing with the similar topics, published by authors at ICERI 2016 and 2018 conferences. The studying of the matrices is an attractive illustration of the application of the ideas and techniques of linear algebra in our everyday live. The basic matrix operations in the matrix theory, such as addition, subtraction, multiplication, inverse, calculation of the determinant of the matrix and the like, are separately quite easy to understand for students. Unfortunately, the application of these techniques are already difficult and the students have a big problems with solving of the practical examples, in which the matrix operations appears. Consequently, the aim of this paper is to show some simple practical applications which are suitable for teaching the theory of the matrices and call attention to the most common student’s mistakes in solving of these problems. All applications will be solved using the matrices and it will be also accompanied by a Matlab script and if possible also presented graphically. All presented applications were used in teaching of mathematics especially linear algebra at Faculty of Transport Engineering, University of Pardubice and they can be used as an inspiration for teaching at the other universities with the same or similar focus.
Matice ve vzdělávání budoucích dopravních inženýrů s podporou softwaru Matlab
Keywords: matrix; matice; applied mathematics; errors; linear algebra; matlab; aplikovaná matematika; chyby; lineární algebra; Matlab